Pharmacological justification of the composition of active ingredients in the composition of «Molozol» gel - L. M. Maloshtan; I. M. Grubnik; Yu. V. Yudina; D. L. Veliky (The State Expert Center of the Ministry of Health of Ukraine, 2023)
Today, in connection with the rapid increase in the number of skin diseases complicated by secondary microbial and fungal infection, the creation of new drugs with a complex dermatomycosis effect for their local use is gaining particular relevance. In modern dermatological practice, mostly soft dosage forms are used. The wide use of soft medicinal forms is due to the presence of some advantages: high local concentration in the skin, relative economy and manufacturability of these means. However, on the modern Ukrainian pharmaceutical market, the range of drugs with a complex dermatomycosis effect is limited. This makes it necessary to find new means for local application in dermatitis with complicated fungal pathology. The aim of our research is an experimental ground of rational composition of operating substances in a gael under the conditional name «Molozol» for treatment of dermatomycoses. Gel was prepared on general rules by preparations of soft medical forms. Taking into account physical and chemical properties of operating substances, in particular their solubility, sucking, salicylic and sorbic acid was entered as a solution in propylene glycol and entered in the basis procured in advance for gel. With the aim of ground of rational concentration milk, salicylic and sorbic acid in the combined gel of «Molozol», and also study of his biological activity were conducted microbiological and toxicological. Determination of the antibacterial properties of the gel was carried out by diffusion in agar using reference strains of microorganisms Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885/653. The rational composition of the active substances of the gel under the conventional name «Molosol» for the treatment of dermatomycosis was experimentally substantiated. Based on the data of microbiological studies, the concentration of active substances - lactic acid, salicylic acid and sorbic acid in the composition of the gel «Molosol» was justified. With the combination of active substances salicylic acid 8%, lactic acid 10%, for sorbic acid concentration 0.5%, «Molosol» gel shows the most pronounced antimicrobial and fungicidal activity against the tested strains of microorganisms. The index of acute toxicity when applied to the skin of animals was determined, which proved that the developed soft drug «Molosol» in the form of a gel belongs to the IV class of low-toxic substances. The combined gel «Molosol» is promising for further research as an antimicrobial and antifungal agent with keratolytic properties.